Enter the Matrix: Building Creative Industry through Delivering Insights in Comics - Hafiz Ahmad Aziz; Alvanov Zpalanzani; Setiawan Sabana (Journal of Visual Art and Design, 2013)
Comic is a media which delivers its content through visual sequence. This media has negative preference in Indonesia's community because viewed as mild entertainment for children. Yet in modern society, comics observed and researched as one of media which could penetrate deep within its reader's mind. In re-create cultural insight through comic, the content must encrypt into visual and sequential mode which form a matrix of insight. This matrix will encompasses the effective transformation of cultural content in comic and also other visual media through media linkage strategy. The media linkage strategy is to surround the children's access of information and visual entertainment in order to build certain knowledge and understanding. It's a system that crystallized from global marketing practices of visual media industry over decades. This paper urges to highlight the visual communication design study in creating a matrix of cultural insight in translating cultures of Archipelago and media linkage strategy in order to strengthen cultural understanding among children.